Synthesis of 1,2,3-Triazolylmethoxyphenyl[1,2,4]triazolo[1,2-a]indazoletrione Derivatives by Combining Click and Multicomponent Reactions - Zolfigol, Mohammad Ali; Khazaei, Ardeshir; Faal-Rastegar, Toktam; Mallakpour, Shadpour; Khavasi, Hamid Reza; Salehi, Peyman; Fakharian, Mahsa (Synthesis, 2016)
The one-pot four-component reaction of propargylated benzaldehydes, azide, dimedone, and urazoles in the presence of melamine trisulfonic acid, copper acetate, and sodium ascorbate was used for the synthesis of 1,2,3-triazolylmethoxyphenyl[1,2,4]triazoloindazole-1,3,8-trione derivatives as novel compounds.
Keywords: multicomponent reactions; click chemistry; 1,2,3-triazoles; melamine trisulfonic acid (MTSA); urazoles